Corpus Optimization: Socialization and Training of English Teachers in Islamic Boarding Schools : Optimalisasi Korpus: Sosialisasi dan Pelatihan Guru Bahasa Inggris di Pondok Pesantren - Agustina, Yulia Agustina; Prasetianingrum, Ary; Riadi Jaelani, Selamet (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
The goal of the two-days "Socialization and Training of English Teachers" program at the Darul Muttaqien Islamic Boarding School Education Foundation (YP3DM) was to increase teacher proficiency in the teaching of English by utilizing corpus technology. Training methods included talks, panel discussions, and practical experience with corpus applications. Participants are invited to understand the concepts of concordance, collocation, synonymy and word pronunciation and how to integrate them in teaching. The implications of this activity show that such training not only enriches teachers' understanding of the use of technology in learning, but also improves students' ability to master English more effectively. This activity also contributes to the professional development of teachers and the improvement of the quality of English education in the digital era.